The Impact of Tunneling on the Subthreshold Swing in Sub-20 nm Asymmetric Double Gate MOSFETs - Hak Kee Jung; Sima Dimitrijev (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper analyzes the subthreshold swing in asymmetric double gate MOSFETs with sub-20 nm channel lengths. The analysis of the carrier transport in the subthreshold region of these nano scaled MOSFET includes tunneling as an important additional mechanism to the thermionic emission. It is found that the subthreshold swing is increasing due to tunneling current and that the performance of nano scaled MOSFETs is degraded. The degradation of the subthreshold swing due to tunneling is quantified using analytical potential distribution and Wentzel–Kramers–Brillouin (WKB) approximation in this paper. This analytical approach is verified by two dimensional simulation. It is shown that the degradation of subthreshold swing increases with both reduction of channel length and increase of channel thickness. We also show that the subthreshold swing is increasing in case of different top and bottom gate oxide thicknesses.